Salivary tumour necrosis factor-alpha as a diagnostic marker of desquamative gingivitis (Bangladesh Journal of Medical Science, 2024)
Background Desquamative gingivitis (DG) is a non-plaque induced gingival disease. Clinical examination coupled with histopathological and immunofluorescence studies diagnose it, however, diagnosis of about one-third of DG cases is still elusive which leads to poor clinical outcomes. Therefore, biomarker profiling of DG will help in predicting better treatment outcomes. The objective of the study was to evaluate the salivary TNF-α as a biomarker of DG and compare it with chronic gingivitis (CG) and clinically healthy (CH) subjects.Materials and Methods A case-control study was done with 94 subjects having; DG (n=31), chronic gingivitis CG (n=31), and clinically healthy CH (n=32) were recruited in the study after they fulfilled subject selection criteria and signed the consent form. Detailed history and clinical examination were done. Subjects were told to abstain from eating 2 hours before saliva collection. Three ml of saliva was collected in the saliva collection tubes between 9 AM to 12 PM. The collected samples were stored at -80 centigrade and TNF-α levels were assessed employing an ELISA technique (R&D systems). The data were analyzed using SPSS (Version 20, IBM, USA) statistical software.Results Salivary TNF-α levels were significantly increased in DG (33.71±12.15 pg/ml,) as compared to CH (5.99±2.11) and CG (13.48±1.16 pg/ml) subjects. The receiver operating curve (ROC) of DG for salivary TNF-α biomarker showed an area under the curve (AUC) of 0.973.Conclusion Salivary TNF-α is a good diagnostic biomarker that is significantly increased in desquamative gingivitis.Bangladesh Journal of Medical Science Vol. 23 No. 02 April’24 Page : 484-490